Dissociation of clinical symptoms and magnetic resonance imaging data in axial psoriatic arthritis - A. O. Vasilieva; D. E. Filipenko; E. V. Kapustina; N. V. Popov; P. A. Shesternya (Современная ревматология)
Currently, there is no generally accepted definition of axial lesions in psoriatic arthritis (axPsA), and the diagnostic criteria are extrapolated from the recommendations for ankylosing spondylitis and axial spondyloarthritis.Objective: To evaluate data of magnetic resonance imaging (MRI) of spine and sacroiliac joints (SIJ) in patients with psoriasis complaining of chronic back pain of any cause.Material and methods. 143 patients were enrolled to the study, including 57 (39.9%) men and 86 (60.1%) women, median age – 47 [36; 57] years, mean duration of psoriasis was 17.4±13.4 years. In all patients, the agreement of the existing symptoms with the inflammatory back pain (IBP) criteria of A. Calin et al., M. Rudwaleit et al. and ASAS was checked. All patients underwent MRI of the spine and SIJ, determination of ESR, CRP levels, HLA-B27 and consultations with a dermatologist and a rheumatologist.Results and discussion. An association of bone marrow edema (BME) in the spine and SIJ with nail involvement (odds ratio, OR 2.32; 95% confidence interval, CI 1.12–4.81; p=0.035), palmoplantar psoriasis (OR 3.85; 95% CI 1.43–10.41; p=0.054) and a weak correlation with PASI (r=0.329, p=0.034) was found. There were no statistically significant differences in PASI between patients with BME and without BME. In patients with IBP who fulfilled the criteria of A. Calin et al., osteitis in the SIJ was present in 19 (34.5%; OR 2.79; 95% CI 1.26–6.19; p=0.01); Berlin criteria of 4 signs – 25 (28.7%; OR 2.42; 95% CI 1.00–5.84; p=0.045); Berlin criteria of 3 signs – in 18 (24.0%; OR 1.12; 95% CI 0.51–2.44; p=0.783); ASAS criteria – in 17 (34.0%; OR 2.48; 95% CI 1.12–5.49; p=0.023). In almost half of the patients with BME in the spine or SIJ, the symptoms did not fulfil the criteria for IBP. Signs such as the presence and duration of morning stiffness had a high prognostic value. Isolated spondylitis (presence of BME in vertebrae and absence of BME in SIJ) was rarely found in patients with IBP fulfilling various criteria (in 4.0–8.1% of cases).Conclusion. Considering the existing discrepancy between symptoms and MRI results, it is necessary to develop independent tools for screening and early diagnosis of axPsA.